2019
DOI: 10.17511/jopm.2019.i03.09
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological study of lymph node lesions: a study of 250 cases

Abstract: Introduction: Lymph node enlargement is frequent presentation in all age groups with a wide spectrum of diseases, ranging from infections to malignancy. Therefore, management of cases depends on lymph node pathology, which can be studied by collecting material through fine needle aspiration method that can be used as an outpatient procedure. Objectives: The study was undertaken to assess the cytomorphological features and incidence of various lymph node diseases on fine-needle aspiration cytology (FNAC) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Reddy et al study showed that cervical and axillary group had 1-2cm size, > 1.5cms in the inguinal region and >0.5 cm at any other site are to be considered significant [18] . In our study tuberculosis lymphadenitis was the most common cause with most of the cases seen in the age group 30-50 years as compared with other studies Patel's AS et al study [13] , it was seen in third and fourth decade.The study done by Shilpa et al [19] and Kochhar et al [20] also found the highest incidence of Tuberculous lymphadenitis. Highest incidence of tuberculosis lymphadenitis cases due to the low socioeconomic status, poverty, illiteracy.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Reddy et al study showed that cervical and axillary group had 1-2cm size, > 1.5cms in the inguinal region and >0.5 cm at any other site are to be considered significant [18] . In our study tuberculosis lymphadenitis was the most common cause with most of the cases seen in the age group 30-50 years as compared with other studies Patel's AS et al study [13] , it was seen in third and fourth decade.The study done by Shilpa et al [19] and Kochhar et al [20] also found the highest incidence of Tuberculous lymphadenitis. Highest incidence of tuberculosis lymphadenitis cases due to the low socioeconomic status, poverty, illiteracy.…”
Section: Discussionsupporting
confidence: 55%
“…In our study, Lymphoma was seen in 2/100 (2%) cases, one patient's age was 30 years and other patient was 28 years both are Males. Cytomorphological diagnosis was Non Hodgkins Lymphoma in comparison with Mohanty et al [11] showing 3.66% and Patel's A.S et al [13] study 2.07% respectively. Flow cytometer and immunohistochemistry in adjunct to FNAC will help in the diagnosis of NHL.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar finding was seen in a study done by Malhotra et al 18 where cervical region (71.7%) was the most affected one followed by axillary region (11.1%). Patel et al 19 also found the cervical lymph node (68.4%) as the most common finding followed by submandibular (10.8%), supraclavicular(10%) and axillary (5.2%) lymph nodes.…”
Section: Discussionmentioning
confidence: 88%
“…This finding was similar to other studies done in Nepal and different parts of India. [19][20][21] Reactive lymphadenitis 113 (34.1%) was the most common diagnosis followed by tubercular lymphadenitis 53 (16%). Several studies done in Nepal also showed reactive lymphadenitis as the most common diagnosis.…”
Section: Discussionmentioning
confidence: 99%